LA LANGUE AND PAROLE IN LITERATURE: CURRICULUM AND MATERIALS DEVELOPMENT - Fabiola Dharmawanti Kurnia (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2013)
AbstraksThis paper presents the scope and dimension of literature curriculum and material developments from the axis of Saussurean notion of la langue and parole and also demonstrates the application of curriculum theory and practice to literature teaching. The teaching of works of literature employs reading and interpretation, instigating with the text - ’la langue’ and moving to the context - ‘parole’. Effective literature teaching materials are teachers’ own materials which enhance students’ learning experience.